A STUDY OF DWELLING TIME AT TANJUNG PERAK HARBOR SURABAYA INDONESIA - Dharmakarja, I Gede Made Artha; Wardana, Dzulham Faruq Rifqi (Unit Penerbitan Politeknik Keuangan Negara STAN, 2024)
The research aims to determine the factors that influence dwelling time at Indonesian ports so that the government can make policies for releasing imported goods at ports more quickly and efficiently. This study uses secondary data obtained from KPPBC TMP Tanjung Perak quantitative data in the form of monthly pre-clearance, customs clearance, post-clearance, and dwelling time processing times from January 2020 to December 2022. Statistical analysis using the linear regression method uses the application SPSS. Based on the results of the analysis of the factors that influence dwelling time, it is concluded that the pre-clearance, customs clearance, and post-clearance processes simultaneously have an influence on dwelling time at the port of Tanjung Perak. Meanwhile, partially, the pre-clearance and post-clearance processes have a positive and significant effect on dwelling time, while the customs clearance process does not affect dwelling time. Currently, the customs clearance process is faster due to new policies and improved facilities. This research only discusses the management of imported goods, so other research using export variables is needed to increase the accuracy and efficiency of government trade policies.